Sustainable Local Product Development for Coastal Tourism at Cemara Beach, West Lombok Regency - Masrun Masrun; Helmy Fuady; Titi Yuniarti; Rizal Kurniansah; M. Firmansyah (Goodwood Publishing, 2026)
Purpose: This study aims to identify the characteristics of local products, examine key constraints in their development, and formulate an integrated model for coastal tourism–based local product development to support sustainable local economic development in the Cemara Beach Area, West Lombok. Research Methodology: A qualitative case study approach was used. Data were collected through in-depth interviews, direct observations, and documentation involving MSME actors, tourism managers, community groups and government representatives. The data were analyzed using thematic analysis with triangulation to ensure the validity of the findings. Results: The findings revealed that local products consist of both tangible goods (seafood-based culinary and processed marine products) and intangible services (mangrove and religious tourism, camping grounds, and homestays). These products contribute to income generation, employment, and livelihood diversification in the region. However, their development is constrained by limited production capacity, low innovation, weak quality standardization and packaging, restricted market access, limited digital marketing adoption and weak stakeholder coordination. Conclusions: Local products play a strategic role in shaping tourism experiences and destination identities. Sustainable development requires an integrated approach involving MSME empowerment, strengthened destination governance, coastal ecosystem conservation, and integrated marketing strategies. Limitations: This study is limited to a single case study area and relies on qualitative methods, which may limit the generalizability and quantitative measurement of impacts. Contributions: This study contributes to the literature by proposing an integrative, destination-level development model applicable to coastal tourism in developing countries.